A Systematization of Police Arrests of Senegalese Population in the City of Buenos Aires from a Spatial Perspective - Abiuso, Federico Luis (2022)
In this article, we propose to analyze the interactions between the security forces and the Senegalese population that take place on public roads in the Autonomous City of Buenos Aires (CABA). The methodology includes the systematization of quantitative data from reports from various institutions, as well as interviews with people from the community since it is relevant to recover their own voices and perception. The results reveal situations of institutional violence that weigh heavily on the community of Senegalese origin as part of racialization relations that occur with greater force in two areas of the city.